The effect of low-skill immigration restrictions on US firms and workers: Evidence from a randomized lottery - Michael A. Clemens; Ethan G. Lewis (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
The U.S. limits work visas for low-skill jobs outside of agriculture, with a binding quota that firms access via a randomized lottery. We evaluate the marginal impact of the quota on firms entering the 2021 H-2B visa lottery using a novel survey and pre-analysis plan. Firms exogenously authorized to employ more immigrants significantly increase production (elasticity +0.16) with no decrease or an increase in U.S. employment (elasticity +0.10, statistically imprecise) across several pre-registered subsamples. The results imply very low substitutability of native for foreign labor in the policy-relevant occupations. Forensic analysis suggests similarly low substitutability of black-market labor.
Keywords: F22; J61; D22; 330